2021
DOI: 10.1016/j.ijnss.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and health-promoting behaviors among older adults living with different health statuses: A cross-sectional study

Abstract: Objectives To describe the characteristics and relationships of social isolation and health promoting behaviors of Chinese older adults with different health statuses. Methods Totally 485 older adults were recruited. They were divided into three groups based on their health status: healthy group ( n = 72), group with one disease ( n = 183) and group with multimorbidity ( n = 230). Lubben So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Although quite a few studies conducted in China have identified the negative effects of social isolation on late-in-life depression, most constructed social isolation with a single measure (e.g., marital or cohabiting status) or multiple measures (e.g., family size, living with a spouse, frequency of contact with children, rural residence, participation of social activities) (49). Our findings advanced prior studies by adopting a reliable and valid instrument: the LSNS-6, which has been indicated as a good tool to screen for social isolation among older, community-dwelling Chinese adults (38). Furthermore, the results demonstrate isolation (e.g., infrequent contact with others) in both family and friendship ties was significantly associated with more depressive symptoms as well as cognitive impairment among Chinese older adults.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although quite a few studies conducted in China have identified the negative effects of social isolation on late-in-life depression, most constructed social isolation with a single measure (e.g., marital or cohabiting status) or multiple measures (e.g., family size, living with a spouse, frequency of contact with children, rural residence, participation of social activities) (49). Our findings advanced prior studies by adopting a reliable and valid instrument: the LSNS-6, which has been indicated as a good tool to screen for social isolation among older, community-dwelling Chinese adults (38). Furthermore, the results demonstrate isolation (e.g., infrequent contact with others) in both family and friendship ties was significantly associated with more depressive symptoms as well as cognitive impairment among Chinese older adults.…”
Section: Discussionsupporting
confidence: 78%
“…In the CLASS questionnaire, the measure of social isolation was adapted from the Lubben Social Network Scale ( 37 ), then validated in Chinese older adults ( 38 ). Participants were asked two sets of questions about family and friendship ties, with three items in each set.…”
Section: Methodsmentioning
confidence: 99%
“…This study showed that health-promoting behavior partially mediated between social isolation and IC, which was consistent with previous study results (31). The social network, as an important environmental factor, significantly influences the healthpromoting behavior of the older adults.…”
Section: Discussionsupporting
confidence: 92%
“…7,18,29 These behavioural pathways were also supported in the present study. An alternative explanation is that socially isolated Chinese older adults are less engaged in social activities and healthpromoting activities (eg physical activity, spiritual growth and stress management), 30 which could negatively affect oral health. 19 In this study, we found that functional health was a major pathway linking social isolation and tooth loss.…”
Section: F I G U R E 2 Flow Diagram Of Included and Excluded Particip...mentioning
confidence: 99%